Evidence of zoonotic chlamydophila psittaci transmission in a population at risk in zulia state, venezuela (2012)
Objective This study was aimed at investigating the frequency of infection by Cp. psittaci and determining its genotype in individuals at potential risk of exposure to the bacteria. Methodology The study involved 170 individuals: a risk group (n= 96) and a low-risk control group (n=74). Cp. psittaci was detected and genotyped by single-tube nested PCR and ompA gene sequencing. Results Eight (8.3 %) positive cases were detected in the risk group and 1 (1.4 %) in the control group (p